Management of a Space for Speech and Analysis of the Conditions for the Production of Versions regarding a Corporate Crime: the Case of the Vale S/A B1 Dam Failure in Brumadinho (MG) - Alves, Elizeu Barroso (Organizações & Sociedade, 2023)
This paper analyzes how the construction occurred of the conditions for the production of versions of the corporate crime related to the Vale S/A dam failure in Brumadinho (MG) based on an analysis of the final report of the Parliamentary Commission of Inquiry of the Chamber of Deputies (CPI Bruma). This study provides a specific contribution by presenting corporate crime as a crime legitimized by management, in which the dynamic of organizations operated under its logic influences the criminal practices as it exerts pressure for economic results at any cost. Thus, our study aimed to analyze how the construction occurred of the conditions for the production of versions regarding the corporate crime and the discursive dynamic around the corporate crime of Vale S/A in Brumadinho (MG), in the CPI Bruma. Methodologically, we sought to use documental research in the investigative process and the final report of the CPI Bruma, created specifically to investigate the failure of the B1 dam at the Córrego do Feijão mine, applying discourse analysis from a habermasian perspective, seeking to demonstrate that communicate practices may be intentionally distorted to favor one group to the detriment of another. With this, we analyzed the management of the space for speech in the CPI, through the habermasian lens, the multiple discourses, under the premises of the validity intentions of the act of speech, and its communicative distortions. We provide indications from the CPI Bruma report that suggest that the failure of the B1 dam at the Córrego do Feijão mine was not an accident, but occurred because of the negligence of Vale S/A, which, in pursuing financial success, chose to prioritize economic results and ignore the imminent danger of failure.